INNOVATIVE MODEL OF APPLICATION OF OWN FINANCIAL RESOURCES IN THE PROCESS OF SELF-FINANCING AGRICULTURE (INNOVATIVE ECONOMY, 2024)
Khalatur S.M., Omelnytska Yu.I. INNOVATIVE MODEL OF APPLICATION OF OWN FINANCIAL RESOURCES IN THE PROCESS OF SELF-FINANCING AGRICULTUREPurpose. The aim of the article is to define an innovative model of using one's own financial resources in the agricultural sector to increase the efficiency of self-financing and ensure the sustainable development of agricultural enterprises.Methodology of research. The use of methods of analysis and synthesis made it possible to determine modern methods and principles of financing innovative activities of enterprises. Conducting generalizations revealed the main advantages and disadvantages of using individual components of own financial resources in the process of self-financing of innovative development of agrarian enterprises. Tabular and graphic methods allowed to visually display the current state of sources of financing of agricultural enterprises in Ukraine. Findings. It was revealed that currently the main method of financing Ukrainian farmers is self-financing, and retained earnings play a key role among the sources of own financial resources. The gradual increase in the amount of profit capitalization has a positive effect on the expanded reproduction of agricultural production, but these funds are not enough to ensure large-scale and costly innovative projects. A model of financing the innovative development of agricultural enterprises through the use of a combined set of financing sources is proposed, in which self-financing should play a key role. It has been proven that when financing the innovative development of the agrarian sector, support from the state is critically necessary.Originality. The methods and principles of financing innovative activities are summarized, which made it possible to form a model of financing innovative development of agrarian enterprises. The advantages and disadvantages of using individual components of the own financial resources of agrarian enterprises in modern economic conditions are determined, which will allow to create competitive advantages for agrarians through the combination of methods of financing innovative transformations in the future.Practical value. The theoretical and methodological provisions of this study deepen the practical toolkit of effective management of one's own financial resources and contribute to the development of innovative processes in the agricultural sector.Key words: innovations, own capital, self-financing, profit capitalization, depreciation.
Keywords: innovations; own capital; self-financing; profit capitalization; depreciation.